The problems on method in Aristotle - Meléndez Acuña, Germán (Estudios de Filosofía, 2001)
This paper provides an introductory overview of what Aristotle’s interpreters dealing with the question of method in his work have been discussing as the main problem to be solved: the problem regarding the relation between Aristotle’s theory of demonstrative science (as staled in the Posterior Analytics) and Aristotle ’s research praxis (as displayed in his own scientific treatises), a praxis which interpreters often describe as dialectic.